Dermatologic Findings in Renal Transplant Recipients: Possible Effects of Immunosuppression Regimen and p53 Mutations - TURAN, KADİR; ATA, PINAR (ELSEVIER SCIENCE INC, 2010)
Objective. To analyze the dermatologic lesions and possible effects of immunosuppression treatment and p53 gene mutations on dermatologic findings in renal transplant recipients. Materials and Methods. The study included 163 renal transplant recipients. After dermatologic examination, cultures, and histopathologic and genetic analyses were performed. A single-strand conformation polymorphism technique was used to analyze p53 gene mutations. Patients were categorized into 3 groups according to time since the transplantation procedure. Results were analyzed using the chi(2) test, using a software program (SPSS version 13.0; SPSS, Inc, Chicago, Illinois). Results. Mean (SD) age of the 163 transplant recipients (65 women and 98 men) was 40 (11) years, and posttransplantation follow-up was 65 (55) months. The most frequently observed drug-related lesion was hypertrichosis, in 46 of 150 patients. Of 115 lesions, the most commonly observed were verruca vulgaris (n = 34) from viruses, and pityriasis versicolor (n = 21) from superficial fungal infections. Of the total group, 20 patients (12.2%) were mutation carriers. Compared with the entire cohort, the group with premalignant lesions demonstrated more p53 mutations (11% vs 50%; P = .004). Patients given cyclosporine therapy exhibited more premalignant or malignant cutaneous lesions compared with patients who received other agents (P = .03). Conclusion. Patients carrying p53 mutations developed a malignant lesion in the late posttransplantation period, which suggests the importance of prediction of risk.
Keywords: SKIN DISEASES; CUTANEOUS MANIFESTATIONS; FOLLOW-UP; CANCER; POSTTRANSPLANT